ANALISIS PERBEDAAN KUALITAS AKUNTANSI DAN TATA KELOLA SEBELUM DAN SETELAH PENERAPAN PSAK KONVERGENSI IFRS - Neva - Novianti; Daniati Puttri - Puttri (JURNAL PUNDI, 2019)
The International financial reporting standard (IFRS) is an international financial reporting standard that aims to make financial reports comparable and have a high level of reliability. Indonesia carried out the full implementation of the term 'coverage' in 2012. Thus, it is expected that the accounting quality will be better after the implementation, as well as the governance practices. This study aims to find out empirically, whether there are differences in accounting quality as measured by earnings quality and accounting conservatism and governance before and after the application of PSAK that refers to IFRS. This research uses companies listed on the Indonesia Stock Exchange, especially consumer groups from 2008 to 2015 (2008-2011 before full adoption of IFRS and in 2012-2015 after full adoption of IFRS). There are 18 companies that fit the criteria. The hypothesis test results show that there is no difference in accounting quality based either on earnings quality or conservatism before and after the implementation of IRFS. However, governance shows a difference between before and after the implementation of IFRS.